2020
DOI: 10.1002/apj.2565
|View full text |Cite
|
Sign up to set email alerts
|

On modelling of glucose transport in hollow fibre membrane bioreactor for growing three‐dimensional tissue

Abstract: Hollow fibre membrane bioreactors (HFMBs) have been shown to overcome the diffusion limitation of nutrients (e.g., glucose) from the hollow fibres (lumens) to the porous regions of a scaffold (extracapillary space). However, direct monitoring of glucose diffusion inside the HFMBs is almost impossible because of their small size; thus, various computational modelling frameworks have been developed in the past. These models have defined that the glucose diffusivity in the cell culture medium used in the HFMBs wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This effect is important due to its potential in limiting the glucose concentration, which is essential for cell growth in the scaffold region. In agreement with [ 29 ], the current work also showed that the lowest concentration will occur at the largest value of R . This is due to an increase in diffusion distance from the inlet ( c = 1) toward the outlet of the bioreactor.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…This effect is important due to its potential in limiting the glucose concentration, which is essential for cell growth in the scaffold region. In agreement with [ 29 ], the current work also showed that the lowest concentration will occur at the largest value of R . This is due to an increase in diffusion distance from the inlet ( c = 1) toward the outlet of the bioreactor.…”
Section: Resultssupporting
confidence: 92%
“…This can be attributed to the increase in the diffusion distance of glucose due to the increase in the bioreactor length. The results in this paper demonstrated similar trends when compared to [ 29 ] for a similar combination of porous materials and therefore are not shown in this paper. However, it suffices to note that the bioreactor length should be considered carefully, keeping in mind the glucose transfer limitation while developing a larger bioreactor scale, especially for a long-term culture process within the scaffold region.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations